Ethnomedicinal Plant Diversity and Local Knowledge in Legok Raina Village, Bogor Regency, West Java, Indonesia - Priyanti, Priyanti; Jori, Binar Setiawan; Aminudin, Iwan; Dasumiati, Dasumiati; Junaidi, Junaidi (RUMPHIUS, 2026)
The community of Legok Raina Village in Bogor Regency, West Java, continues to rely on medicinal plants for daily healthcare practices. This study aimed to inventory and identify medicinal plant species and document the plant parts used, preparation methods, therapeutic functions, and ailments treated, as no previous research has been conducted in this area. Data were collected through semi-structured interviews with one traditional healer (tabib), two traditional birth attendants (paraji), and 27 general respondents selected by community leaders, complemented by plant specimen collection, observation, and documentation. The data were analyzed using the Use Value (UV) index to determine the relative importance of each species. A total of 104 species belonging to 93 genera and 46 families were recorded, with Zingiberaceae as the most dominant family, comprising 12 species from 8 genera. Shrubs represented the most common growth form (39 species), and leaves were the most frequently utilized plant part. Ageratum conyzoides showed the highest UV (1.760), whereas Lactuca sativa, Piper sarmentosum, and Kadsura scandens had the lowest (0.003). Approximately 60% of respondents continue to preserve ancestral knowledge and actively participate in conservation efforts. These findings highlight the cultural and therapeutic significance of traditional medicinal plants in the study area.